The Epipalaeolithic (Iberomaurusian) at Grotte des Pigeons (Taforalt), Morocco: A preliminary study of the land Mollusca - Tayor, V; Barton, R; Bell, M; Bouzouggar, A; Collcutt, S; Black, S; Hogue, J (2011)
Land snail middens occur widely throughout the circum-Mediterranean, particularly in the Maghreb and Libya, but are relatively understudied when compared with the better known coastal marine middens. The site of Taforalt (Grotte des Pigeons) in north east Morocco contains thick ashy deposits with considerable numbers of land snails, dating between 13,000 and 11,000 BP. The site has been excavated periodically since its discovery in 1908, but little attention has been paid to the land snail component. Recent excavations at the site as part of the Cemeteries and Sedentism Project has facilitated reinvestigation of the Iberomaurusian layers, including the upper ashy midden unit. This investigation addresses questions surrounding chronological variation in the lithic assemblage, subsistence strategies, population health and mortuary practices. Preliminary work on the land snails has identified a low species diversity in the grey series midden layers, characterised by the large edible species Alabastrina alabastrites, Helix cf aspersa, Dupotetia dupotetiana, Otala punctata and Cernuella sp, which appear to represent an abrupt intensification in the use of land snails as a food source. Significant quantities of associated plant material and animal bone suggest that land snails are part of a broader based diet which is adopted from around 13,000 BP. © 2011 Elsevier Ltd and INQUA.